On Taxonomic Position of Some Horsefly Species (Diptera, Tabanidae) from Talysh - Andreeva, R.V.; Zeynalova, Z.A. (Вестник зоологии, 2002)
Atylotus talyschensis sp. n. is described; it is similar to A. rusticus ochraceus Olsufjev et Melnikova, differing by elongate appendage of R4 vein, abdomen coloration, shape of frontal calluses and 3rd antennal joint. Species rank is given to Ò. terterjani Andreeva et Dolin, 1982 (originally described in subspecies rank, as Tabanus canipalpis terterjani Andreeva et Dolin), based upon comparison with characters of nominotypical subspecies.